Internet user and economic selected Southeast Asia nations: a panel data analysis / Noorhamizah Abdul Wahab, Sabri Nayan and Yong Kang Cheah - Abdul Wahab, Noorhamizah; Nayan, Sabri; Cheah, Yong Kang (Universiti Teknologi MARA, 2020)
There has been an increasing interest among academicians about the relationship between the internet user and economic growth. The adoption of the internet creates an effective platform of business trade that provides expediency and convenience in doing business globally and thus results in tremendous dependency on technology to expand business locally and internationally. Hence, the use of the internet plays a crucial role in the economic development of a country and undoubtedly, to a certain extent, affects the economic growth of a nation. This paper aims to examine the relationship between the internet user and economic growth in seven selected Southeast Asia countries. Panel Autoregressive Distributed Lag (ARDL) (PMG) model is employed in examining the relationship between the internet user and economic growth from the year 1997 to 2013. Consistent with the endogenous growth theory proposed by Romer (1986), this study reveals that internet user and trade positively and significantly affect the economic growth in selected Southeast Asia countries. The increase in the use of internet thus is philanthropic to the users and can lead to faster economic growth. Internet improves the standard of living of an individual.